Karakteristik Somatotype dan Body Composition Atlet Renang Flam Aquatics Club Kota Kediri - Mohamad Ilham Agil Tri Saputra; Anna Noordia; Indra Himawan Susanto; Mokhamad Nur Bawono (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the characteristics of somatotype and body composition of swimmers from Flam Aquatics Club in Kediri City. A quantitative descriptive approach was used with a cross-sectional study design. The sample consisted of 10 swimmers aged 9–17 years, selected through purposive sampling. Somatotype was measured using the Heath-Carter method, while body composition was assessed using a Bioelectrical Impedance Analysis (BIA) scale. Data analysis was performed using Microsoft Excel 2012. The results showed that male swimmers were predominantly of the Central somatotype (4 athletes), while female swimmers were evenly distributed between Endomorphic Ectomorph and Ectomorphic Endomorph types (2 athletes each). The average body composition of male swimmers included muscle mass of 34.48 kg, bone mass of 1.88 kg, fat mass of 5.07 kg, and body fat percentage of 10.65%. For female swimmers, the average muscle mass was 27.7 kg, bone mass 1.5 kg, fat mass 5.25 kg, and body fat percentage 15.08%. It can be concluded that male athletes tend to have a Central somatotype, while female athletes are equally divided between two somatotype categories. The highest bone and fat mass in female athletes was found in those with the Ectomorphic Endomorph type.